Thermal Comfort Evaluation of Low-Cost Rental Flats in a Coastal Tropical Area - Rizka Felly; Andina Syafrina; Reza Arlianda (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2026)
Low-cost rental flats in Indonesia face significant thermal discomfort challenges due to high humidity and reliance on natural ventilation. This study evaluates the thermal environment of Kampung Nelayan II Sungailiat low-cost rental flat to understand housing quality in humid tropical coastal areas. Using a quantitative approach, measurements of air temperature, humidity, and wind speed were conducted in 11 residential units. Data were analyzed using the Thermal Humidity Index (THI) and CBE Adaptive Method. Results reveal a discrepancy: THI categorized all units as uncomfortable, while CBE simulations identified eight units as comfortable. Discussion suggests that while THI is a useful indicator of heat stress, it is limited in accounting for human physiological adaptation and airflow. The study concludes that the CBE Adaptive Model is more suitable for evaluating local thermal tolerance. Design strategies must prioritize passive cooling, specifically optimized building orientation and cross-ventilation.